Agency, structure, and international politics : from ontology to empirical inquiry - Friedman, Gil, 1966- (Routledge advances in international relations and politics, 1997)
This book is the first in depth study of the concepts of agency and structure in the context of international realtions and politics. It is an important contribution to the study of international relations and politics.